The antiviral activity of arctigenin in traditional Chinese medicine on porcine circovirus type 2. (June 2016) - Chen, Jie; Li, Wentao; Jin, Erguang; He, Qigai; Yan, Weidong; Yang, Hanchun; Gong, Shiyu; Guo, Yi; Fu, Shulin; Chen, Xiabing; Ye, Shengqiang; Qian, Yunguo
Abstract: Arctigenin (ACT) is a phenylpropanoid dibenzylbutyrolactone lignan extracted from the traditional herb Arctium lappa L. (Compositae) with anti-viral and anti-inflammatory effects. Here, we investigated the antiviral activity of ACT found in traditional Chinese medicine on porcine circovirus type 2 (PCV2) in vitro and in vivo. Results showed that dosing of 15.6–62.5 μg/mL ACT could significantly inhibit the PCV2 proliferation in PK-15 cells (P < 0.01). Dosing of 62.5 μg/mL ACT 0, 4 or 8 h after challenge inoculation significantly inhibited the proliferation of 1 MOI and 10 MOI in PK-15 cells (P < 0.01), and the inhibitory effect of ACT dosing 4 h or 8 h post-inoculation was greater than 0 h after dosing (P < 0.01). In vivo test with mice challenge against PCV2 infection demonstrated that intraperitoneal injection of 200 μg/kg ACT significantly inhibited PCV2 proliferation in the lungs, spleens and inguinal lymph nodes, with an effect similar to ribavirin, demonstrating the effectiveness of ACT as an antiviral agent against PCV2 in vitro and in vivo. This compound, therefore, may have the potential to serve as a drug for protection of pigs against the infection of PCV2. Highlights: ACT could significantly inhibit the PCV2 proliferation in PK-15 cells. ACT inhibits PCV2 proliferation in mouse models of infection. ACT significantly inhibited PCV2 proliferation in the lung, spleen and inguinal lymph nodes.